2008
DOI: 10.4161/cc.7.20.6882
|View full text |Cite
|
Sign up to set email alerts
|

FoxO1 integrates insulin signaling to VLDL production

Abstract: Very low-density lipoproteins (VLDL) are triglyceride-rich particles. VLDL is synthesized in hepatocytes and secreted from the liver in a pathway that is tightly regulated by insulin. Hepatic VLDL production is stimulated in response to reduced insulin action, resulting in increased release of VLDL into the blood under fasting conditions. Circulating VLDL serves as a vehicle for transporting lipids to peripheral tissues for energy homeostasis. Conversely, hepatic VLDL production is suppressed in response to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(83 citation statements)
references
References 159 publications
1
81
1
Order By: Relevance
“…In the present study, we showed that at 1 y of age term born SGA children have a high prevalence of high triglycerides, with the cut-off value based on term born AGA children from the same population. The high prevalence of high triglycerides is probably caused by reduced insulin sensitivity, as insulin resistance in the liver results in very low-density lipoprotein overproduction and development of hypertriglyceridemia (16,17). In this small group, this hypothesis could not be confirmed with the HOMA values.…”
Section: Discussioncontrasting
confidence: 49%
“…In the present study, we showed that at 1 y of age term born SGA children have a high prevalence of high triglycerides, with the cut-off value based on term born AGA children from the same population. The high prevalence of high triglycerides is probably caused by reduced insulin sensitivity, as insulin resistance in the liver results in very low-density lipoprotein overproduction and development of hypertriglyceridemia (16,17). In this small group, this hypothesis could not be confirmed with the HOMA values.…”
Section: Discussioncontrasting
confidence: 49%
“…FoxO1 is a transcription factor that plays a key role in the hepatic VLDL assembly and secretion. FoxO1 stimulated the MTTP expression, elevated the ApoB secretion, and augmented the VLDL production though binding and stimulating MTTP promoter activity (Kamagate and Dong, 2008a;Kamagate et al, 2008b). Hepatic steatosis occurs in birds when the increase of lipogenesis exceeds the rate of VLDL assembly and secretion.…”
Section: Discussionmentioning
confidence: 99%
“…In hypertriglyceridemia, more VLDL particles, as measured by apoB, and larger and more TG-and apoC-III-enriched lipoproteins are found [49][50][51]. Hepatic insulin resistance may contribute to a high production rate of VLDL because insulin reduces apoB synthesis and VLDL secretion in the liver [52,53]. Although insulin resistance is associated with high triglycerides, VLDL and TG concentrations can be similar in patients with widely divergent insulin sensitivity [54,55].…”
Section: Hypertriglyceridemia As a Major Component Of Atherogenic Dysmentioning
confidence: 99%